TOURIST POTENTIAL OF THE TERRITORY AS A BASIS FOR SUSTAINABLE TOURISM DEVELOPMENT - KULYNIAK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The level of sustainable tourism development depends on the tourist potential of the territory, in particular on the provision of historical and cultural heritage sites, natural and climatic resources, the wealth of customs and traditions, which, in combination with human and infrastructural support, form the potential for the development of various types and forms of tourism and recreation. The analysis of scientific approaches has shown that the basis of the tourist potential of the territory is the set of tourist resources (natural, historical and cultural, infrastructural, etc.) and conditions (social, economic, marketing, etc.), as well as the possibility of their further use for the sustainable tourism development in this territory. It is proposed to consider the tourist potential of the territory as a structure of three components: 1. Natural resource potential: natural resources and natural conditions. 2. Historical and cultural potential: historical and cultural material tourist resources and historical and cultural intangible tourist resources (intangible heritage). 3. Socio-economic potential: tourist infrastructure facilities, human resources and marketing potential. The relationship between the structural components of tourism potential and the specifics of tourism services formed on their basis is considered. It is proposed to divide types of tourism into components of the tourist potential of the territory, depending on which component is the object for organizing a tourist trip and forms the basis for forming a tourist service, in particular: 1) nature-oriented tourism – tourism associated with visiting natural tourist facilities; 2) cultural-oriented tourism – tourism associated with visiting historical and cultural tourist facilities and using intangible cultural heritage objects; 3) service-oriented tourism – tourism associated with attracting tourist infrastructure facilities. Taking into account the different provision of tourist resources and tourist infrastructure facilities in different regions, the correct assessment of the tourist potential of the territory becomes an important strategic task for the sustainable tourism development of these regions.
Keywords: tourist resources; natural resource potential; historical and cultural potential; socio-economic potential; types of tourism; tourist infrastructure; intangible heritage